Hydrochemical of Groundwater for Al Dammam unconfined Aquifer within Al-Salman Basin, Al-Muthana Governorate, South West Iraq - Al-Sheikh, Osamah N.; AL-Shamma’a, Ayser M. (Iraqi Journal of Science, 2019)
The quality of groundwater is just as important as its quantity. The kinds and concentration of salts in groundwater depend on the environment, movement, and the source of the groundwater. During the field work, 20 samples have been collected from water wells from Al-Salman basin for two seasons represent wet and dry seasons in November 2017 and April 2018. After water well samples have been analyzed the Electrical conductivity values range from (2260 to 5500) Î¼S/cm for dry season and range from (2540 to 5630) Î¼S/cm for wet season, the Total dissolved solids values range from (1289 to 3582) ppm for dry season and range from (1710 to 3960) ppm for wet season, and pH values range from (7.11 to 7.3) for dry and wet seasons. The Hydrochemical classification which applied using Piper’s Diagram revealed there are three type of water (sulphate type Ca+2 â€“ Mg+2 â€“ Cl- â€“ SO4, sulphate type Ca+2 â€“ Mg+2 â€“ Cl- - SO4, NaCl), and two water type by applying Chadha’s diagram (sulphate type Ca+2 â€“ Mg+2 â€“ Cl- - SO4, Na+- Cl-), the variation of water type in the study area due to influence of Rus Formation which consists of anhydrite, and structure roles where made precipitation concentrate in Al-Salman depressions and streams flow faults that ended with playa.